1996
DOI: 10.1148/radiology.198.3.8628887
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide--enhanced versus gadolinium-enhanced MR imaging for differential diagnosis of focal liver lesions.

Abstract: AMI-25 decreased the SI of benign tumors and helped differentiate benign from malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(86 citation statements)
references
References 0 publications
4
74
1
7
Order By: Relevance
“…For instance, Kupffer cells loaded by nanoparticles migrate through normal liver tissue and cause hypointense signal on T2-weighted images, whereas due to the lack of Kupffer cells in the tumor, malignant regions retain their original intensity and can be easily distinguished. 5,52 In the case of liver lesion induced by O. felineus, the same situation occurs. The damaged liver zones, formed predominantly around bile ducts, did not accumulated nanoparticles.…”
mentioning
confidence: 82%
“…For instance, Kupffer cells loaded by nanoparticles migrate through normal liver tissue and cause hypointense signal on T2-weighted images, whereas due to the lack of Kupffer cells in the tumor, malignant regions retain their original intensity and can be easily distinguished. 5,52 In the case of liver lesion induced by O. felineus, the same situation occurs. The damaged liver zones, formed predominantly around bile ducts, did not accumulated nanoparticles.…”
mentioning
confidence: 82%
“…Further, the absence of Kupffer cells in malignancies has been exploited to allow for enhanced accuracy in discerning between healthy and diseased tissue through SPIO endowed contrast. 117,133,149 In addition to the detection and characterization of liver lesions, larger nanoparticles such as SHU555A and AMI-25 have also been shown capable of detecting focal splenic tumors. 5,157,160 Reimer et al, in imaging hepatic lesions, clearly show the power of enhanced detection through the use of SPIO, 117 ( Fig.…”
Section: Liver and Splenic Imagingmentioning
confidence: 99%
“…Several authors have reported the presence of Kupffer cells in HCCs, especially in wHCC, but these can be confused with benign nodules in SPIO-enhanced MRI [2,4]. The characterisation of focal liver lesions by means of PSIL is considered problematic because the PSILs from several lesion types show an overlap [7,[11][12][13]. In particular, some studies reported an overlap between the PSILs of benign lesions and those of wHCC [7,11,13].…”
Section: Discussionmentioning
confidence: 99%